High-Intense Interval Training Prevents Cognitive Impairment and Increases the Expression of Muscle Genes FNDC5 and PPARGC1A in a Rat Model of Alzheimer's Disease - Nogueira Godinho, Welton D.; Vasconcelos Filho, Francisco Sérgio Lopes; Pinto, Daniel Vieira; Alves, Juliana Osório; de Souza Nascimento, Tyciane; de Aguiar, Isabele Dutra; Silva Almeida, Guilherme Nizan; Ceccatto, Vânia Marilande; Soares, Paula Matias (Current Alzheimer Research, 2022)
Background: Alzheimer's disease is the most common neurodegenerative disease in the world, characterized by the progressive loss of neuronal structure and function, whose main histopathological landmark is the accumulation of β-amyloid in the brain. Objective: It is well known that exercise is a neuroprotective factor and that muscles produce and release myokines that exert endocrine effects in inflammation and metabolic dysfunction. Thus, this work intends to establish the relationship between the benefits of exercise through the chronic training of HIIT on cognitive damage induced by the Alzheimer's model by the injection of β amyloid1-42. Methods: For this purpose, forty-eight male Wistar rats were divided into four groups: Sedentary Sham (SS), Trained Sham (ST), Sedentary Alzheimer’s (AS), and Trained Alzheimer’s (AT). Animals were submitted to stereotactic surgery and received a hippocampal injection of Aβ1-42 or a saline solution. Seven days after surgery, twelve days of treadmill adaptation followed by five maximal running tests (MRT) and fifty-five days of HIIT, rats underwent the Morris water maze test. The animals were then euthanized, and their gastrocnemius muscle tissue was extracted to analyze the Fibronectin type III domain containing 5 (FNDC5), PPARG Coactivator 1 Alpha (PPARGC1A), and Integrin subunit beta 5 (ITGB5-R) expression by qRT-PCR in addition to cross-sectional areas. Results: The HIIT prevents the cognitive deficit induced by the infusion of amyloid β1-42 (p < 0.0001), causes adaptation of muscle fibers (p < 0.0001), modulates the gene expression of FNDC5 (p < 0.01), ITGB5 (p < 0.01) and PPARGC1A (p < 0.01), and induces an increase in peripheral protein expression of FNDC5 (p < 0.005). Conclusion: Thus, we conclude that HIIT can prevent cognitive damage induced by the infusion of Aβ1-42, constituting a non-pharmacological tool that modulates important genetic and protein pathways.
Keywords: Aβ1-42